Koronary heart disease clinical course, post-infarction remodeling, psychological status, and hospitalization time in patients with various ACE genotypes - I. A. Melentyev; A. A. Vershinin; E. A. Kolesnikova; A. S. Melentyev; N. A. Malygina; I. V. Kostomarova; V. P. Zaitsev (Российский кардиологический журнал, 2006)
Clinical, instrumental and psychosomatic associations of ACE gene insertion/deletion (I/D) polymorphism were studied in inpatients with coronary heart disease (CHD): unstable angina (UA) - 32, myocardial infarction (MI) - 80. The control group included 66 healthy volunteers (CG). ACE gene D allele was more prevalent than I allele (p < 0.02) in CHD and MI patients. These groups also had significant difference in DD genotype prevalence, comparing to CG (p < 0.05). According to echocardiography results, severe left ventricular hypertrophy (IVH) was associated with DD genotype. According to psychometry data, patients with DD genotype had increased levels of total hostility and Type A behavior manifestation than patients with ID or II genotype (p < 0.05). Prolonged hospitalization time in MI patients with DD genotype was significantly associated with severity of Type A behavior and various hostility components (p < 0.05).